Economic evaluation of bailing capsules for patients with diabetic nephropathy in China - He, Yumei; Li, Wei; Zhu, He; Han, Sheng (Frontiers in Pharmacology, 2023)
Background: Diabetic nephropathy is a major microvascular complication and the main cause of end-stage renal disease in diabetic patients. The therapeutic effects of Bailing capsules for diabetic nephropathy have already been demonstrated; however, the cost-effectiveness of Bailing capsules remains controversial. This study aimed to evaluate the cost-effectiveness of Bailing capsules combined with Western medicine compared with Western medicine alone in diabetic nephropathy from a Chinese healthcare system perspective. Methods: A Markov model was established to simulate the disease process of patients over a 20-year period. Clinical efficacy data were obtained from a meta-analysis, and transition probability was estimated based on microsimulation. Direct costs and utility values were collected from the Chinese Drug Bidding Database (https://www.shuju.menet.com.cn) and published literature. The incremental cost-effectiveness ratio (ICER) was measured, and one-way and probabilistic sensitivity analyses were performed to observe model stability. Results: A total of 34 randomized controlled trials involving 3,444 patients with diabetic nephropathy were selected for the meta-analysis. Compared to Western medicine alone, the addition of Bailing capsules resulted in an increase of 0.39 quality-adjusted life-years (QALYs) and additional costs of Chinese Yuan (CNY) 24,721, yielding an ICER of CNY 63,001 per QALY gained. The ICER was lower than the threshold of willingness-to-pay of CNY 80,976 (The GDP per Capita in China). The reliability and stability of the results were confirmed by the sensitivity analysis. Conclusions: We found that Bailing capsules may be a cost-effective treatment choice for patients with diabetic nephropathy in the Chinese population.